SEMIOTICS STUDY ON SKRIPSI'S MEMES - Fahmiyah Dwi Lestari; Shanty A.Y.P.S Duwila; Yeni Probowati (EL2J (English Language and Literature Journal), 2022)
This study is conducted to analyze semiotics on meme dealing with skripsi. This study is aimed at explaining the denotative meaning and connotative meaning of each meme of dealing with skripsi. The writer uses a qualitative approach and content analysis as the research method. The sources of data are 5 selected memes taken from internet, such as Instagram, Twitter, Facebook, digital news media and web. The data are collected by searching the meme dealing with skripsi on internet such us Instagram, Facebook, Twitter digital news media and web which contain semiotics, then screenshotting the meme dealing with skripsi, and finally choosing the meme dealing with skripsi to be analyzed, while the procedure of data analysis are first selecting the meme dealing with skripsi that have been collected, then classifying the meme dealing with skripsi, after that describing denotative and connotative meaning of each meme of dealing with skripsi using Roland Barthes’ theory of semiotics and the last is drawing the conclusion. In this research, all meme dealing with skripsi have the denotative and connotative meaning. Most of them are about the difficulties of students in writing skripsi.